Protein dysregulation associated with Alzheimer's disease and its clinical diagnosis - Oliveira Guimarães, Larissa (2024)
Alzheimer's Disease (AD) is a neurodegenerative condition characterized by the accumulation of beta-amyloid and tau proteins, leading to cognitive decline and dementia. Lysosomal system dysfunction is a critical factor in the pathogenesis of the disease, contributing to the buildup of misfolded proteins. Early detection of AD is crucial, and biomarkers such as tau protein and Aβ have shown promise for diagnosis in the early stages. Thus, the objective of this work is to explore the pathophysiology of AD, with an emphasis on beta-amyloid and tau proteins, and to discuss the diagnostic and therapeutic implications associated with these biomolecules. The study methodology consisted of an integrative literature review, focusing on AD and its pathological mechanisms. Initially, searches were conducted in the PubMed and BVS databases, resulting in the identification of 16 articles on PubMed and 173 on BVS. After applying filters related to language (English and Portuguese), full-text availability, and publication period (last 10 years), 14 articles were selected for inclusion in the review. The results indicate that the deposition of β-amyloid plaques and neurofibrillary tangles are hallmark pathological features of AD. γ-secretase, a crucial enzyme in the processing of amyloid precursor protein, plays a central role in the formation of β-amyloid peptides, which are associated with neurodegeneration. The discussion emphasizes the importance of therapeutic interventions targeting these proteins to slow the progression of the disease. Therefore, the need for new diagnostic and therapeutic strategies based on a deeper understanding of AD’s cellular and molecular mechanisms is highlighted, aiming to improve the quality of life for patients and provide more effective management of the condition.